(untitled) (Biocenosis, 2025)
This study describes an environmental education experience carried out in Rocha, Uruguay, focused on water quality analysis as an integrating axis for scientific and environmental content. The initiative was developed by faculty from the Centro Universitario Regional del Este (CURE) in collaboration with the city’s three public high schools, involving students aged 14 to 16. The proposal was structured in three sessions: theoretical training and sampling techniques, experimental laboratory work and results analysis, collective reflection, and learning evaluation. A mixed methodology was applied, combining diagnostic and final assessment tools with standardized kits for the determination of physicochemical and microbiological parameters. The results showed significant improvements in students’ knowledge and interest in environmental topics, as well as the identification of varying levels of contamination in local water sources, which prompted spaces for critical discussion. In a second phase, a group of students participated as cofacilitators in a session for future teachers, consolidating their acquired knowledge. This experience highlights the value of contextualized and collaborative pedagogical approaches to promote meaningful learning, strengthen interinstitutional links, and foster the construction of environmental citizenship.